Social Relationships and Depression: Ten-Year Follow-Up from a Nationally Representative Study - Teo, Alan R.; Choi, HwaJung; Valenstein, Marcia (PLOS ONE, 2013)
Background Social network characteristics have long been associated with mental health, but their longitudinal impact on depression is less known. We determined whether quality of social relationships and social isolation predicts the development of depression. Methods The sample consisted of a cohort of 4,642 American adults age 25–75 who completed surveys at baseline in 1995–1996 and at ten-year follow-up. Quality of relationships was assessed with non-overlapping scales of social support and social strain and a summary measure of relationship quality. Social isolation was measured by presence of a partner and reported frequency of social contact. The primary outcome was past year major depressive episode at ten-year follow-up. Multivariable logistic regression was conducted, adjusting for the presence of potential confounders. Results Risk of depression was significantly greater among those with baseline social strain (OR, 1.99; 95% CI, 1.47–2.70), lack of social support (OR, 1.79; 95% CI, 1.37–2.35), and poor overall relationship quality (OR 2.60; 95% CI, 1.84–3.69). Those with the lowest overall quality of social relationships had more than double the risk of depression (14.0%; 95% CI, 12.0–16.0; p<.001) than those with the highest quality (6.7%; 95% CI, 5.3–8.1; p<.001). Poor quality of relationship with spouse/partner and family each independently increased risk of depression. Social isolation did not predict future depression, nor did it moderate the effect of relationship quality. Conclusions Quality of social relationships is a major risk factor for major depression. Depression interventions should consider targeting individuals with low quality of social relationships.